Efektivitas Pembelajaran Mandiri Menggunakan Aplikasi SCI Media Online Pada Siswa Kelas V SD Negeri 2 Watuaji - Wijayanto, Satio Mustiko; Fathurohman, Irfai; Fajrie, Nur (Universitas Muria Kudus, 2024)
The research was carried out at SDN 2 Watuaji, Keling Jepara in 2024. This research was based on the low motivation of students in independent learning. The percentage above the KKM score for class V students at SDN 2 Watuaji in the 2nd Midterm Test is still 50%. To overcome this problem, teachers apply the use of the SCI Media Online application. The SCI Media Online application is an application in the form of a Learning Management System (LMS). This research focuses on increasing student learning scores and shows how fifth grade students at SDN 2 Watuaji become more motivated to study independently after learning using the SCI Media Online program. The conclusions of this research are first, after utilizing the SCI Media Online program, fifth grade students at SDN 2 Watuaji experienced an increase in their enthusiasm for independent learning, from low to high or from 10.6 to 17.0. Second, after learning using the SCI Media Online program, class V students at SDN 2 Watuaji experienced an increase in the minimum completion proportion in the Final Semester II Examination by 50%, from 50% to 100%.